ANALISIS KONSTRUKTIVISME TERHADAP DISRUPSI KONSTRUKSI PENGETAHUAN SISWA AKIBAT OVERLOAD INFORMASI DIGITAL DALAM PEMBELAJARAN - Desvita Putri Kirana; M.Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
The development of digital technology has significantly increased students' access to information, but this condition has also given rise to the phenomenon of information overload, which impacts the learning process. This study aims to analyze the disruption of students' knowledge construction due to exposure to digital information from a constructivist perspective. The method used is a secondary data-based case study by reviewing various scientific journals and recent educational reports. The analysis shows that massive and unstructured information reception leads to students' understanding being partial and unintegrated. The constructivist process is disrupted, particularly in the mechanisms of assimilation and accommodation, as well as in the reduction of social interaction that plays a role in scaffolding. High cognitive load also hinders in-depth information processing, resulting in superficial understanding. The constructivist approach, through problem-based learning, inquiry, reflection, and collaboration, can improve students' knowledge construction process. These findings indicate that learning needs to be directed toward active and structured cognitive activities in order to optimally enhance the quality of students' understanding.